Integrasi Higher Order Thinking Skill (HOTS) dengan Model Creative Problem Solving - Abd Hamid Wahid; Rizka Afkarina Karimah (MODELING: Jurnal Program Studi PGMI, 2018)
Creative Problem Solving (CPS) becomes one of alternatives for educators to develop HOTS. It is because CPS is a learning model centered on problem-solving skills, followed by strengthening the creativity and thinking skill of learners to master high-level thinking skills. This study discussed the integration of higher order thinking skill (HOTS) through creative problem solving (CPS). This research used qualitative method of case study type with the site of Madrasah Tsanawiyah Nurul Jadid Paiton Probolinggo. It focused on fiqih subject. The result showed that there is an increasing of students 'learning motivation, the increasing of students' learning interest and the process of teaching and learning is very fun to create joyful learning.